1995
DOI: 10.1111/j.1467-8624.1995.tb00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neonatal Stress Reactivity

Abstract: The question of whether a sexually dimorphic stress reaction exists prior to extensive socialization was addressed by examining sex differences in physiological and behavioral stress reactivity, in healthy, term neonates, after a mildly stressful behavioral assessment procedure. The Neonatal Behavior Assessment Scale (NBAS; Brazelton, 1973) was administered to 18 male and 18 female neonates. Heart rate (HR), salivary cortisol, and behavioral states were assessed before and after the exam. Sex differences inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
5
35
1
2
Order By: Relevance
“…While sex differences in cortisol reactivity have been reported for both neonates (Davis & Emory, 1995) and adults (Kirschbaum et al, 1992), our finding contrasts with previous reports in the literature of a lack of reported gender differences in cortisol levels in 6-month-old infants (Buss et al, 2003; Haley & Stansbury, 2003). While Haley and Stansbury (2003) reported lower heart rates in 5- and 6-month-old boys than girls, the direction consistent with lower cortisol, they found no gender differences in cortisol.…”
Section: Discussioncontrasting
confidence: 99%
“…While sex differences in cortisol reactivity have been reported for both neonates (Davis & Emory, 1995) and adults (Kirschbaum et al, 1992), our finding contrasts with previous reports in the literature of a lack of reported gender differences in cortisol levels in 6-month-old infants (Buss et al, 2003; Haley & Stansbury, 2003). While Haley and Stansbury (2003) reported lower heart rates in 5- and 6-month-old boys than girls, the direction consistent with lower cortisol, they found no gender differences in cortisol.…”
Section: Discussioncontrasting
confidence: 99%
“…In this sample of healthy African American neonates, obstetrical experiences were not associated with significant differences in HRV. Although there was a low rate of breast-feeding and a high rate of circumcision in this urban sample, we replicated previous studies that have shown that breast- versus bottle-feeding results in higher HRV (DiPietro et al, 1987) and that circumcision results in lower heart rate (Davis & Emory, 1995). In the final regression analysis, past maternal depression history, feeding method, and circumcision contributed to unique variance in neonatal HRV.…”
Section: Discussionsupporting
confidence: 87%
“…Although the relationship between gonadal hormones and the HPA axis in adults is complex and not clearly understood, a few studies have also reported sex differences in basal cortisol levels during childhood, prior to the pubertal increases in gonadal hormones. Thus, boys have higher basal cortisol levels than girls in some studies (Davis & Emory, 1995; Elmlinger, et al, 2002; Ouellet-Morin, et al, 2010); but opposite findings have also been reported (Essex, et al, 2002; Koupil, et al, 2005; Sondeijker, et al, 2007). The differing results may reflect differences in the age at which boys and girls were sampled.…”
mentioning
confidence: 81%